The Psalter in the Canon - Jeppesen, Knud (HTS teologiese studies, 2003)
The Psalter, read as a coherent book instead of being read as 150 independent poems, reveals some patterns and a continuum of ideas, which might not express the editors’ original intention, but support the readers’ understanding of this canonical book. The article suggests that, even if the majority of texts are laments, the Psalter is a book of praise, underlined for instance by the endings of the Psalter’s five books. The five books relate the Psalter to the Pentateuch, and a form of competition between David and Moses is found (see esp Book 4), of which David was the winner. This is one of the reasons why the Christians were able to read the Psalter as a Christian book.